2013
DOI: 10.1016/j.ijsu.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticojejunostomy by reinforcing the pancreas without covering the anastomotic line reduces pancreatic fistula

Abstract: Applying PGA felt pasting to PJ anastomosis could be one effective measure for reducing POPF after PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The PGA mesh was used in many surgical procedures, for the prevention of CSF leakage during dura repair of spine and for hemostasis of splenic rupture . This finding was in good agreement with other studies showing the efficacy of PGA mesh after pancreatic resection .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The PGA mesh was used in many surgical procedures, for the prevention of CSF leakage during dura repair of spine and for hemostasis of splenic rupture . This finding was in good agreement with other studies showing the efficacy of PGA mesh after pancreatic resection .…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, the efficacy of PGA mesh in PD remains unclear. Although two studies reported that PGA mesh significantly reduced POPF rates after PD (5.6% vs. 38.9%, P = 0.016 [13]; and 39.1% vs. 70.0%, P = 0.042 [14]), a third study found that PGA mesh had no effect on POPF (34% vs. 44%, P = 0.355) [15]. The present study was therefore designed to investigate the ability of PGA mesh to reinforce the pancreaticojejunostomy anastomosis after PD, finding that PGA mesh significantly reduced rates of POPF and especially of clinically relevant POPF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ten studies [ 7 12 , 14 17 ] reported overall POPF, 2 studies [ 8 , 15 ] reported that PGA mesh decreased the incidence of POPF, and 8 studies reported no significant association. [ 7 , 9 – 12 , 14 , 16 , 17 ] Moderate heterogeneity ( I 2 = 35%, P = .13) was detected, so we chose a random-effect model to pool the data (RR = 0.76, 95% CI = 0.64–0.89, P = .0009). Overall, the pooled data demonstrated that the POPF in the PGA group was significantly lower than the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Each POPF is classified as grades A, B, or C based on the ISGPF criteria as follows: grade A, POPF is clinically stable and requires no treatment or admission; grade B, POPF shows fluid collection on CT scan and may require treatment and/or readmission; and grade C, POPF requires treatment or reoperation, and sepsis or infection may be present [ 7 ]. In this study, only grade B or C POPFs were considered clinically significant POPFs because there were no differences between cases with grade A POPFs and without fistulas in terms of clinical findings and progression [ 8 9 ]. Drains were kept in place for at least 5 days after surgery, and the properties and volume of the drained fluid were recorded.…”
Section: Methodsmentioning
confidence: 99%